Doped zirconium dioxide / copper oxide composite catalyst as well as preparation method and application thereof

Through the preparation of doped zirconium dioxide/cubic oxide composite catalyst, the problem of poor stability of copper-based oxides in acidic electrolyte is solved, and efficient CO2 reduction reaction and catalyst stability are achieved, which improves Faraday efficiency and selectivity.

CN119121304AActive Publication Date: 2024-12-13ZHEJIANG UNIV

Patent Information

Application Number
CN202411133688.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-13
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

In acidic electrolyte, the poor stability of copper-based oxides and the serious problems with the competitive reaction hydrogen evolution caused by high proton concentration limit the efficiency of CO2 reduction reaction and the stability of the catalyst.

Method used

By preparing doped zirconium dioxide/copper oxide composite catalysts, using hydrothermal reaction and transition metal nitrate doping technology, transition metal doped zirconium dioxide/copper oxide catalysts are formed to enhance catalytic activity and stability, and through adjustment The pH value and calcination conditions ensure the adhesion density of the transition metal on copper oxide and electron transport, forming a stable Cu-O covalent bond.

Benefits of technology

The activity and stability of the catalyst are significantly improved in the acidic electrolyte, the Faraday efficiency and selectivity of the CO2 reduction reaction are improved, and the service life of the catalyst is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121304A_ABST
    Figure CN119121304A_ABST
Patent Text Reader

Abstract

The invention discloses a doped zirconium dioxide / copper oxide composite catalyst and a preparation method and application thereof.The preparation method comprises the steps that sodium hydroxide, basic zirconium carbonate and transition metal nitrate are added into deionized water to obtain a mixed solution, the mixed solution is subjected to a hydrothermal reaction and then diluted to obtain a reaction solution, H2O2 is added into the reaction solution, and the doped zirconium dioxide / copper oxide composite catalyst is obtained. Centrifuging and drying to obtain a reaction product; adding water into the reaction product to form a turbid liquid, adding a copper nitrate trihydrate solution into the turbid liquid, adding a sodium carbonate aqueous solution to adjust the pH value to 9-10, and then stirring, standing, carrying out suction filtration, drying and roasting to obtain the transition metal doped zirconium dioxide / copper oxide catalyst. The transition metal doped zirconium dioxide / copper oxide catalyst prepared by the preparation method has relatively high catalytic activity and relatively high stability in an acidic electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a doped zirconium dioxide / copper oxide composite catalyst and a preparation method and application thereof. Background Art

[0002] As the consumption of traditional fossil fuels leads to the continuous increase of carbon dioxide (CO2) in the atmosphere, the greenhouse effect is becoming more and more serious. In recent years, the use of electrochemical reduction technology to convert CO2 to produce clean fuels or platform chemicals while solving environmental pollution problems has received widespread attention.

[0003] Compared with the traditional thermal catalytic conversion of CO2, the electrochemical reduction of CO2 can occur at room temperature and pressure, and this reaction uses electricity as an energy source, which is a feasible sustainable energy development strategy. Effective electrochemical reduction of CO2 is highly dependent on catalysts with high activity, high selectivity and high stability. In the past few decades, many electrocatalysts have been studied, including metal catalysts, molecular pyridine catalysts, etc. for use in CO2RR. Of all the metals studied so far, only copper shows a unique ability to catalyze carbon dioxide to produce hydrocarbons with high Faraday efficiency, and the products are distributed in formic acid, hydrocarbons and alcohols.

[0004] The invention patent application with the publication number CN116065182A discloses a method for preparing a carbon-supported transition metal single atom material. The material is a transition metal single atom anchored fluorine and nitrogen co-doped carbon nanosheet electrocatalyst (M-CNF SACs), which has a two-dimensional porous nanosheet structure, wherein the nickel single atom anchored fluorine and nitrogen co-doped porous carbon nanosheet (Ni-CNF SACs) is used for electrocatalytic carbon dioxide reduction reaction (CO2RR), and has the characteristics of high catalytic activity, high selectivity and excellent stability. The device includes an anode electrode sheet, a cathode electrode sheet, a cation exchange membrane, an anode chamber electrolyte and a cathode electrolyte; the cathode catalyst is Ni-CNF SACs coated on carbon paper, and the cathode electrolyte is a CO2-saturated potassium bicarbonate solution; the anode catalyst is a three-dimensional porous cobalt diselenide catalyst (CoSe2 / CC) grown in situ on carbon cloth, and the anode electrolyte is an alkaline solution containing glycerol.

[0005] The invention patent application with publication number CN117987869A discloses a bimetallic alloy modified carbon nanosheet material and its preparation method and application. The material is a copper-nickel alloy modified nitrogen-doped ultrathin nanosheet electrocatalyst (CuNi-N-CNS), which has an ultrathin willow-leaf-shaped two-dimensional sheet structure and is used for electrocatalytic carbon dioxide reduction reaction (CO2RR) under acidic conditions, and has the characteristics of ultra-high electrocatalytic activity, good conductivity, high selectivity and excellent stability. The flow cell device includes an anode electrode sheet, a cathode electrode sheet, a proton exchange membrane, an anode chamber electrolyte, a cathode chamber electrolyte and a carbon dioxide gas chamber; the cathode catalyst is CuNiN-CNS coated on carbon paper, and the cathode electrolyte is a potassium chloride solution saturated with carbon dioxide; the anode catalyst is a commercial RuIrTi mesh, and the anode electrolyte is a potassium hydroxide solution.

[0006] The electrolytes disclosed in the above two patents are both neutral or alkaline, but the accumulation of carbonate on the electrode surface and the dissolution loss of CO2 cannot be ignored. Therefore, CO2RR in acidic electrolytes with more stringent conditions has attracted widespread attention, which requires overcoming the problems of poor stability of copper-based oxides in acidic electrolytes and severe competitive reaction hydrogen evolution caused by high proton concentration. Summary of the invention

[0007] The invention provides a method for preparing a doped zirconium dioxide / copper oxide composite catalyst. The transition metal-doped zirconium dioxide / copper oxide catalyst prepared by the preparation method has high catalytic activity and high stability in an acidic electrolyte.

[0008] The present invention provides a method for preparing a doped zirconium dioxide / copper oxide composite catalyst, comprising:

[0009] (1) adding sodium hydroxide, basic zirconium carbonate and transition metal nitrate to deionized water to obtain a mixed solution, subjecting the mixed solution to a hydrothermal reaction and then diluting the solution to obtain a reaction solution, adding H2O2 to the reaction solution, centrifuging and drying the solution to obtain a reaction product;

[0010] (2) adding water to the reaction product to form a suspension, adding copper nitrate trihydrate solution to the suspension, adjusting the pH to 9-10 by adding sodium carbonate aqueous solution, and then stirring, standing, filtering, drying, and calcining to obtain a transition metal-doped zirconium dioxide / copper oxide catalyst.

[0011] The present invention dopes a relatively large amount of transition metal into the zirconium oxide lattice by adding transition metal nitrate, and the use of nitrate avoids the influence of residual ions on electrochemical catalysis.

[0012] The present invention limits the size of zirconium dioxide by adding H2O2, so that more transition metal-doped zirconium dioxide can be attached to copper oxide, thereby improving the catalytic performance.

[0013] The present invention adjusts the pH value to alkaline, thereby forming easily precipitated basic copper carbonate or copper hydroxide, so that the reaction product, that is, transition metal-doped zirconium dioxide, can be deposited on the precipitate, thereby avoiding a large amount of suspended transition metal-doped zirconium dioxide from being drawn away during the filtration process, thereby affecting the attachment amount of transition metal-doped zirconium dioxide on copper oxide, and further affecting the catalytic performance.

[0014] The present invention introduces a transition metal into the zirconium oxide so that the transition metal transfers electrons to the zirconium oxide, thereby enhancing the electron transfer from the zirconium oxide to Cu, thereby converting the metal bond between Cu and O into a more stable covalent bond. Therefore, the Cu-O bond of the catalyst provided by the present invention is not easily destroyed in an acidic electrolyte, thereby having higher catalytic activity and stability.

[0015] Preferably, the mass ratio of the copper nitrate trihydrate to the reaction product is 3.775-8.808:1.

[0016] By controlling the content of copper nitrate trihydrate, the density of transition metal-doped zirconium dioxide attached to copper oxide is higher, so that Cu can receive enough electrons to form a more stable Cu-O covalent bond, and avoid excessive aggregation of copper salts, which makes the transition metal-doped zirconium dioxide too dispersed, resulting in part of Cu receiving fewer electrons and unable to form a stable covalent bond. It is easy to be reduced to low-valent Cu in acidic electrolyte, thereby reducing the catalytic performance.

[0017] Preferably, the mass ratio of the sodium hydroxide, basic zirconium carbonate and transition metal nitrate is 10.000:10.000:0.158-1.283.

[0018] Preferably, when the transition metal nitrate is hydrated indium nitrate, the mass ratio of the sodium hydroxide, basic zirconium carbonate and hydrated indium nitrate is 10.000:10.000:0.200-1.000;

[0019] When the transition metal nitrate is hydrated scandium nitrate, the mass ratio of the sodium hydroxide, basic zirconium carbonate and hydrated scandium nitrate is 10.000:10.000:0.158-0.789;

[0020] When the transition metal nitrate is hydrated yttrium nitrate, the mass ratio of the sodium hydroxide, basic zirconium carbonate and hydrated yttrium nitrate is 10.000:10.000:0.256-1.283.

[0021] By adding an appropriate amount of transition metal nitrate, the transition metal can be sufficiently infiltrated into the zirconium oxide lattice, thus avoiding the appearance of a large amount of transition metal oxides.

[0022] Preferably, the temperature of the hydrothermal reaction is 100-120° C. and the time is 5-7 h.

[0023] Preferably, the concentration of the sodium carbonate aqueous solution is 0.5-1 mol / L.

[0024] Preferably, the calcination temperature is 600-800°C, the time is 4-6h, and the heating rate is 0.5-2°C / min.

[0025] Preferably, the transition metal in the transition metal nitrate is yttrium, scandium or indium.

[0026] On the other hand, the present invention also provides a doped zirconium dioxide / copper oxide composite catalyst, which is prepared by the preparation method of the transition metal-doped zirconium dioxide / copper oxide catalyst.

[0027] On the other hand, the present invention also provides an application of the doped zirconium dioxide / copper oxide composite catalyst in an electrocatalytic carbon dioxide reduction reaction, comprising:

[0028] The reaction area is 2-4 cm 2 In the flow electrolytic cell, add -400~-1000mA / cm 2 Electrolysis is performed under constant current conditions, the cathode electrolyte is a KCl solution with a pH of 1-2, CO2 gas is charged into the cathode electrolyte, the anode electrolyte is a K2SO4 solution with a pH of 1-2, the cathode catalyst is the transition metal-doped zirconium dioxide / copper oxide catalyst, and the anode catalyst is titanium felt.

[0029] Preferably, the concentration of the KCl solution is 2-4M, and the concentration of the K2SO4 solution is 0.2-0.3M.

[0030] Preferably, the CO2 gas flow rate is 40-60 mL / min.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention introduces a transition metal into a zirconium oxide lattice to form a transition metal-doped zirconium dioxide, and adsorbs the transition metal-doped zirconium dioxide on copper oxide to form a heterogeneous structure. The present invention provides electrons to zirconium through the transition metal, so as to enhance the ability of zirconium to provide electrons to Cu, so that the valence state of Cu is close to the valence state of O, so as to enhance the covalency between Cu and O, so that the catalyst provided by the present invention has a relatively stable Cu-O bond, is not easily reduced in an acidic electrolyte, and has better catalytic performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 XRD patterns of the yttrium-doped zirconium dioxide-copper oxide catalyst prepared in Example 1 and the zirconium dioxide-copper oxide catalyst not doped with transition metal prepared in Comparative Example 1;

[0034] Figure 2 The low-magnification and high-magnification TEM photos, mapping diagrams and element distribution diagrams of the yttrium-doped zirconium dioxide-copper oxide catalyst prepared in Example 1 are shown, among which: Figure 2 a is a low-magnification TEM photo. Figure 2 b and Figure 2 c is a high-magnification TEM photo, Figure 2 d is the mapping diagram;

[0035] Figure 3 This is an X-ray absorption fine structure spectrum analysis diagram of the yttrium-doped zirconium dioxide-copper oxide catalyst prepared in Example 1, wherein: Figure 3 a is the X-ray absorption fine structure spectrum analysis diagram of zirconium element, Figure 3 b is the X-ray absorption fine structure spectrum analysis of copper element;

[0036] Figure 4 A Faraday efficiency diagram for the production of ethylene comparing the yttrium-doped zirconium dioxide-copper oxide catalyst prepared in Example 1 and the zirconium dioxide-copper oxide catalyst not doped with transition metal prepared in Comparative Example 1;

[0037] Figure 5 This is a Faraday efficiency diagram for comparing ethylene production of transition metal-doped zirconium dioxide-copper oxide catalysts prepared in Comparative Example 1 and Examples 1, 2, and 3.

[0038] Figure 6 This is a diagram showing the Faraday efficiency of ethylene production of yttrium-doped zirconium dioxide-copper oxide catalysts with different copper loadings prepared in Examples 1 and 4 and Comparative Example 2.

[0039] Figure 7 This is a diagram comparing the Faraday efficiencies of ethylene production from yttrium-doped zirconium dioxide-copper oxide catalysts with different yttrium doping amounts prepared in Examples 1, 5-6 and Comparative Example 3.

[0040] Figure 8 This is a stability test chart of the yttrium-doped zirconium dioxide-copper oxide catalyst prepared in Example 1. DETAILED DESCRIPTION

[0041] The present invention is further described below by means of the accompanying drawings. The embodiments of the present invention are intended to enable those skilled in the art to better understand the present invention, and do not limit the present invention in any way.

[0042] Example 1

[0043] (1) Synthesis of 5wt% yttrium-doped zirconium dioxide (YSZ) nanoparticles:

[0044] A. Dissolve 10 g of sodium hydroxide, 10 g of basic zirconium carbonate and 1.283 g of yttrium nitrate hexahydrate in 20 g of deionized water and add them into a 100 mL hydrothermal kettle.

[0045] B. Heat in a hydrothermal kettle at 110°C for 6 hours.

[0046] C. After cooling, the resulting mixture was transferred to a 100 mL round-bottom flask.

[0047] D. Dilute with 42.5 mL of H2O.

[0048] E. With continuous stirring, add 5.1 mL of H2O2 at 50°C for 5 hours.

[0049] F. Remove excess solution by centrifugation and dry the wet solid overnight.

[0050] (2) Coprecipitation of copper salt on yttrium-doped zirconium dioxide:

[0051] A. Weigh 0.1 g of the above reaction product into a 100 mL round-bottom flask, add 40 mL of ultrapure water, and stir to form a uniform suspension.

[0052] B. Weigh 0.378 g of copper nitrate trihydrate and dissolve it in 12.5 mL of ultrapure water. Slowly add it to the round-bottom flask.

[0053] C. Use 0.5 mol / L sodium carbonate aqueous solution to adjust the pH to 9-10.

[0054] D. Stir for 1 hour.

[0055] E. Turn off stirring and let it stand for 1 hour.

[0056] F. Filter and dry in an oven at 50°C.

[0057] (3) Calcination of the catalyst with copper salt attached: calcination in a muffle furnace at 600°C for 4 hours with a heating rate of 2°C / min.

[0058] Example 2-Example 3

[0059] Different from Example 1, Examples 2 and 3 provide transition metal salts of 0.789 g of scandium nitrate trihydrate and 1.000 g of indium nitrate hydrate, respectively.

[0060] Comparative Example 1

[0061] The difference from Example 1 is that no transition metal salt is added, and the generated product is a zirconium dioxide-supported copper oxide catalyst.

[0062] Performance Analysis:

[0063] like Figure 1 As shown, the XRD patterns of the catalyst and carrier provided in Comparative Example 1 and Example 1 before and after doping with transition metal yttrium showed diffraction peaks of copper oxide and zirconium dioxide, and no diffraction peak of yttrium trioxide was observed. Compared with ZrO2 before doping, the YSZ diffraction peak shifted to a lower angle, indicating that yttrium can be successfully incorporated into the lattice of zirconium dioxide within a reasonable doping amount range.

[0064] from Figure 2 From the dispersion diagram of Cu, Zr and Y in the copper oxide, it can be seen that YSZ with smaller particle size is uniformly present on the surface of copper oxide, such as Figure 2 a, Figure 2 b and Figure 2 As shown in c, there are obvious lattice fringes in the high-magnification TEM photo, indicating that the material has good crystallinity and that there are abundant heterogeneous interfaces between the two.

[0065] like Figure 3 As shown in a, it shows that the addition of yttrium leads to a lower overall valence state of zirconium dioxide, such as Figure 3 As shown in Figure b, after the heterojunction is formed, the copper element obtains a lower electron valence state, indicating that the interaction between the two leads to electron transfer, and the addition of yttrium makes the mutual electron transfer more obvious. After copper obtains electrons, the covalency of the Cu-O bond in the Cu-O-Zr interface is enhanced, the bond length becomes shorter, and it is more stable.

[0066] Application Example 1

[0067] The reaction area is 2 cm 2 In a flowing electrolytic cell, electrolysis was performed under constant current conditions. The cathode electrolyte was a 3M KCl solution with a pH of 1-2. CO2 gas was added to the cathode electrolyte with a CO2 gas flow rate of 30 mL / min. The anolyte was a 0.25M K2SO4 solution with a pH of 1-2.

[0068] The cathode catalysts used in Application Example 1 are the transition metal-doped zirconium dioxide / copper oxide catalysts prepared in Examples 1-3 and the zirconium dioxide / copper oxide catalyst prepared in Comparative Example 1, and the anode catalyst is titanium felt.

[0069] like Figure 4 and Figure 5 As shown, the reaction area is 2cm 2 In the flow electrolytic cell, add -400~-1000mA / cm 2 Electrolysis under constant current conditions, at -800mA / cm 2 At the current density of 545.0 mA / cm, the ethylene Faraday efficiency of the yttrium-doped zirconium dioxide-copper oxide electrolysis reaction provided in Example 1 is as high as 68.7%, and the current density is as high as 545.0 mA / cm 2 Under the same reaction conditions, the Faraday efficiency of ethylene in the electrolysis reaction of the ZrO2 / CuO catalyst provided in Comparative Example 1 is only 51.1%. At the same time, the selectivity of the zirconium dioxide-copper oxide catalyst doped with indium and scandium for ethylene is also improved to a certain extent compared with ZrO2 / CuO.

[0070] like Figure 8 As shown, the stability test of yttrium-doped zirconium dioxide-copper oxide catalyst. In the flow electrolytic cell, -300mA / cm 2 Under the current density, the stability is up to 14h, and the ethylene Faradaic efficiency is maintained at about 43%.

[0071] Example 4, Comparative Example 2

[0072] Compared with Example 1, the mass of copper nitrate trihydrate added in Example 4 and Comparative Example 2 is different, as shown in Table 1:

[0073] Table 1 The mass of copper nitrate trihydrate provided in Example 4 and Comparative Example 2

[0074]

[0075] Application Example 2

[0076] The reaction area is 2 cm 2 In the flow electrolytic cell, add -400~-1000mA / cm 2 Electrolysis was performed under constant current conditions, the cathode electrolyte was a 3M KCl solution with a pH of 1-2, CO2 gas was introduced into the cathode electrolyte, the CO2 gas flow rate was 30 mL / min, and the anolyte was a 0.25M K2SO4 solution with a pH of 1-2.

[0077] The cathode catalysts used in Application Example 2 are yttrium-doped zirconium dioxide / copper oxide catalysts with different copper loadings prepared in Comparative Example 2 and Example 4, respectively, and the anode catalyst is titanium felt.

[0078] Performance Analysis:

[0079] like Figure 6 As shown, at 800mA / cm 2 Under constant current conditions, when the molar ratio of YSZ and CuO provided in Example 1 is 1:0.6, the maximum ethylene Faraday efficiency of 68.7% is obtained, while when the molar ratio of YSZ and CuO provided in Comparative Example 2 is 1:0.3, due to insufficient active sites, the ethylene Faraday efficiency is only 24.1%, and the performance is significantly reduced. When the molar ratio of YSZ and CuO corresponding to Example 4 is 1:0.8, compared with Example 1, CuO agglomerates during the sintering process, resulting in a decrease in the interface density per unit mass, and the ethylene Faraday efficiency is 51.6%, and the performance is reduced.

[0080] Examples 5-6, Comparative Example 3

[0081] The difference from Example 1 is that the doping amount of yttrium is different, as shown in Table 2:

[0082] Table 2 Examples 5-6 and Comparative Example 3 provide different yttrium doping amounts

[0083]

[0084] Application Example 3

[0085] The reaction area is 2 cm 2 In the flow electrolytic cell, add -400~-1000mA / cm 2 Electrolysis was performed under constant current conditions, the cathode electrolyte was a 3M KCl solution with a pH of 1-2, CO2 gas was introduced into the cathode electrolyte, the CO2 gas flow rate was 30 mL / min, and the anolyte was a 0.25M K2SO4 solution with a pH of 1-2.

[0086] The cathode catalysts used in Application Example 3 are the transition metal-doped zirconium dioxide / copper oxide catalysts prepared in Examples 5-6 and Comparative Example 3, respectively, and the anode catalyst is titanium felt.

[0087] Performance Analysis:

[0088] like Figure 7 As shown, compared with the catalysts prepared using Examples 1, 5 and 6, the selectivity of the 10% YSZ / CuO catalyst provided in Comparative Example 3 for ethylene is significantly reduced.

[0089] It should be understood that the embodiments and examples discussed here are for illustrative purposes only and may be modified or altered by those skilled in the art, and all such modifications and alterations should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing a doped zirconium dioxide / copper oxide composite catalyst, It is characterized in that include: (1) adding sodium hydroxide, basic zirconium carbonate and transition metal nitrate into deionized water to obtain a mixed solution, subjecting the mixed solution to a hydrothermal reaction and then diluting the solution to obtain a reaction solution, and adding H 2 O 2 , centrifuge and dry to obtain the reaction product; (2) adding water to the reaction product to form a suspension, adding copper nitrate trihydrate solution to the suspension, adjusting the pH to 9-10 by adding sodium carbonate aqueous solution, and then stirring, standing, filtering, drying, and calcining to obtain a transition metal-doped zirconium dioxide / copper oxide catalyst.

2. The method for preparing the doped zirconium dioxide / copper oxide composite catalyst according to claim 1, It is characterized in that The mass ratio of the copper nitrate trihydrate to the reaction product is 3.775-8.808:

1.

3. The method for preparing the doped zirconium dioxide / copper oxide composite catalyst according to claim 1, It is characterized in that The mass ratio of the sodium hydroxide, basic zirconium carbonate and transition metal nitrate is 10.000:10.000:0.158-1.

283.

4. The method for preparing the doped zirconium dioxide / copper oxide composite catalyst according to claim 3, It is characterized in that When the transition metal nitrate is hydrated indium nitrate, the mass ratio of the sodium hydroxide, basic zirconium carbonate and hydrated indium nitrate is 10.000:10.000:0.200-1.000; When the transition metal nitrate is hydrated scandium nitrate, the mass ratio of the sodium hydroxide, basic zirconium carbonate and hydrated scandium nitrate is 10.000:10.000:0.158-0.789; When the transition metal nitrate is hydrated yttrium nitrate, the mass ratio of the sodium hydroxide, basic zirconium carbonate and hydrated yttrium nitrate is 10.000:10.000:0.256-1.

283.

5. The method for preparing the doped zirconium dioxide / copper oxide composite catalyst according to claim 1, It is characterized in that The temperature of the hydrothermal reaction is 100-120° C. and the time is 5-7 hours.

6. The method for preparing the doped zirconium dioxide / copper oxide composite catalyst according to claim 1, It is characterized in that The concentration of the sodium carbonate aqueous solution is 0.5-1 mol / L.

7. The method for preparing the doped zirconium dioxide / copper oxide composite catalyst according to claim 1, It is characterized in that The calcination temperature is 600-800°C, the calcination time is 4-6h, and the heating rate is 0.5-2°C / min.

8. A doped zirconium dioxide / copper oxide composite catalyst doped zirconium dioxide / copper oxide composite catalyst, It is characterized in that The catalyst is prepared by the method for preparing the doped zirconium dioxide / copper oxide composite catalyst as described in any one of claims 1 to 7.

9. Use of the doped zirconium dioxide / copper oxide composite catalyst according to claim 8 in an electrocatalytic carbon dioxide reduction reaction, It is characterized in that include: The reaction area is 2-4 cm 2 Flow electrolytic cell, plus -400~-1000mA / cm 2 Electrolysis was performed under constant current conditions. The cathode electrolyte was a KCl solution with a pH of 1-2. CO was charged into the cathode electrolyte. 2 gas, the anolyte is K with pH = 1-2 2 SO 4 Solution.

Citation Information

Patent Citations

  • Yttrium-doped zirconium dioxide mesoscopic crystal and preparation method and application thereof

    CN106698511A

Cited By

  • Benzothiadiazole modified monatomic zirconium doped metal copper electrode material and preparation method and application thereof

    CN120505663A

  • A benzothiadiazole modified single-atom zirconium-doped copper electrode material, a preparation method therefor, and an application thereof

    CN120505663B